Introduction (Hematology Meeting Reports, 2009)
Certain immunomodulatory drugs are establishing a role in the treatment of several haematological malignancies, including myelodysplastic syndromes (MDS), multiple myeloma (MM), and chronic lymphocytic leukaemia (CLL). The use of these drugs, together with recent advances in our understanding of the underlying molecular pathways that affect the course of disease, is changing the way we approach the management of patients with haematological malignancies.